Preparation of nanoscale hydrophobic starch and reinforced styrene-butadiene rubber thereof
The nano-level hydrophobic starch prepared and hydrophobically modified by nanoprecipitation method solves the environmental and health problems of existing styrene butadiene rubber reinforcement materials, significantly improves the mechanical properties of styrene butadiene rubber, and provides a renewable, green, Low-cost reinforcement plan.
Patent Information
- Application Number
- CN202411457157.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The reinforcement materials of existing styrene butadiene rubber are mainly carbon black and white carbon black. Carbon black is a fossil resource and the production process is harmful to the environment and health. It is difficult for traditional methods to find renewable and green alternatives.
Nano-precipitation method is used to prepare nano-scale hydrophobic starch, and hydrophobic modification is carried out through reaction with cetyl trimethoxysilane to form nano-scale hydrophobic starch with hydrophobic characteristics, which is used to strengthen styrene butadiene rubber.
The modulus, strength and interface strength of styrene butadiene rubber have been improved, the water absorption of starch has been reduced, and its mechanical properties have been significantly improved. The tensile strength has been increased by more than 110%, and the elongation of break and fixed extension stress have also been significantly improved. Using starch as a reinforcement reduces costs and is fully biodegradable.
Smart Images

Figure CN119264284A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a preparation method of nano-scale hydrophobic starch, the nano-scale hydrophobic starch and its application, and reinforced styrene-butadiene rubber based on the nano-scale hydrophobic starch. Background Art
[0002] Styrene butadiene rubber (SBR) is a synthetic rubber made by copolymerization of butadiene and styrene. Its molecular structure is linear. Due to the presence of benzene rings, styrene butadiene rubber has better physical and chemical properties than polypropylene rubber. It is widely used in automotive parts, seals, medical equipment, transportation and communications. At present, the reinforcing materials of traditional styrene butadiene rubber are mainly carbon black and white carbon black. Among them, the production process of white carbon black consumes a lot of energy; and carbon black is a fossil resource and is non-renewable. At the same time, it will cause health problems to production workers during the production process. Therefore, it is necessary to find a renewable reinforcing agent that conforms to the green development strategy.
[0003] Starch has excellent full biodegradability. The carbon dioxide and water produced by degradation can return to nature without causing pollution to the environment. Starch also has excellent biocompatibility, mechanical properties and processability. It has broad application prospects in many fields such as biomedicine, textiles and clothing, plastic packaging, agriculture, forestry, animal husbandry and fishery. Summary of the invention
[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing nano-scale hydrophobic starch.
[0005] Another object of the present invention is to provide nano-scale hydrophobic starch prepared by the above method.
[0006] Another object of the present invention is to provide an application of the nano-scale hydrophobic starch, particularly in reinforcing styrene-butadiene rubber.
[0007] Another object of the present invention is to provide a reinforced styrene-butadiene rubber based on the nano-scale hydrophobic starch.
[0008] The purpose of the present invention is achieved through the following solutions:
[0009] A method for preparing nano-scale hydrophobic starch is prepared by a nano-precipitation method, comprising the following specific steps:
[0010] (1) Nano-size starch: The starch suspension is gelatinized once, and then amylase is added to perform enzymatic hydrolysis under heat preservation. After refrigeration, the suspension is heated again for secondary gelatinization. After the treatment, the system is added to an ethanol solution to separate and obtain nano-size starch.
[0011] (2) Hydrophobic modification: The nano-sized starch is added to the hydrolyzate of hexadecyltrimethoxysilane and stirred for reaction. After separation and drying, the nano-sized starch is heated under an inert atmosphere to obtain the nano-sized hydrophobic starch.
[0012] In step (1), the concentration of the starch suspension may be 10-15 wt %, and the starch suspension is obtained by dispersing the starch in water.
[0013] In step (1), the starch can be any conventional starch in the art, such as tapioca starch, corn starch, potato starch, etc.
[0014] In step (1), the gelatinization treatment can be performed at 90-98° C. or different temperatures. The gelatinization treatment time can be 20-120 min or different temperatures. The gelatinization treatment is preferably performed in a constant temperature water bath. The gelatinization treatment is preferably performed with continuous stirring.
[0015] In step (1), the insulation temperature may be 50-60°C.
[0016] In step (1), the amount of amylase added may be 7-10 ASPU / g starch.
[0017] In step (1), the amylase may be any conventional enzyme in the art, such as α-amylase, β-amylase, isoamylase, etc.
[0018] In step (1), the enzymatic hydrolysis time may be 6-10 hours.
[0019] In step (1), the cold storage treatment can be carried out at 2-6°C; the treatment time can be 12-48 hours.
[0020] In step (1), the volume ratio of ethanol to water in the ethanol solution may be 3:2-5:0.
[0021] In step (2), the mass ratio of the nano-starch to the hydrolyzate can be 5:100-10:100.
[0022] In step (2), the mass concentration of hexadecyltrimethoxysilane in the hydrolyzate may be 2.5-5‰.
[0023] In step (2), the pH of the hydrolyzate may be 4-6. The pH of the system may be adjusted by using an acid solution, such as hydrochloric acid, acetic acid, sulfuric acid, and a mixed solution thereof.
[0024] Furthermore, the hydrolyzate can be obtained by adding hexadecyltrimethoxysilane (HDS) to an ethanol aqueous solution.
[0025] Furthermore, the hydrolyzate can be obtained by adding hexadecyltrimethoxysilane (HDS) to an ethanol aqueous solution and hydrolyzing for 1-4 hours at a pH of 4-6.
[0026] Furthermore, the volume ratio of ethanol to water in the ethanol aqueous solution may be 2:3-4:1.
[0027] In step (2), the drying may be performed by vacuum drying at room temperature.
[0028] In step (2), the heating treatment can be carried out at 100-120° C. and the treatment time can be 1-5 hours.
[0029] The preparation method of the present invention and separation can be carried out by conventional methods, such as centrifugation, such as centrifugation at 5000-10000 rpm for 1-30 min.
[0030] The preparation method of the invention is simple and the adjustment is mild. The prepared nano-scale hydrophobic starch has a small particle size and stable properties, and effectively solves the problem of serious stickiness of the existing nano-scale starch during alcohol precipitation.
[0031] The present invention also provides a nano-scale hydrophobic starch prepared by the method.
[0032] The present invention also provides application of the nano-scale hydrophobic starch in reinforcing styrene-butadiene rubber.
[0033] The invention also provides a reinforced styrene-butadiene rubber, the components of which contain the nano-scale hydrophobic starch.
[0034] The nano-scale hydrophobic starch of the present invention achieves a small particle size distribution through nano-processing, and a large number of active groups such as hydroxyl groups are distributed on the surface. It is then modified by acid-hydrolyzed HDS and fully combined with HDS to form hydrophobic starch. When applied to the reinforcement of styrene-butadiene rubber, the nano-scale crystalline starch improves the modulus and strength of the reinforcement, and is dispersed in the styrene-butadiene rubber at the nanoscale, with a micro-nano island structure and good reinforcement effect; through efficient hydrophobic modification, long-chain lipids are introduced into the starch surface to further increase the interface strength, while reducing the water absorption of starch, overcoming the defect that the starch absorbs water and swells during use, thereby reducing the performance of styrene-butadiene rubber; the long-chain hydrophobic groups on its surface have good compatibility with styrene-butadiene rubber, on the one hand, improving the dispersion of starch in the rubber group, thereby forming a uniformly dispersed reinforcement structure in the rubber matrix, while retaining more surface active groups, significantly improving the physical and mechanical properties of styrene-butadiene rubber (non-polar rubber), and effectively solving the problem of weak interface bonding between starch and non-polar rubber, so that the mechanical properties of the reinforced styrene-butadiene rubber are significantly improved, the tensile strength is increased by more than 110%, the elongation at break is increased by 59%, and the 100% tensile stress and 300% tensile stress are also significantly improved.
[0035] The invention adopts starch to reinforce styrene-butadiene rubber. The starch used is a low-cost renewable resource. The starch can be used as a reinforcing filler in styrene-butadiene rubber to reduce costs, and the starch is completely biodegradable and green and environmentally friendly. The obtained reinforced styrene-butadiene rubber has significantly improved properties and can be applied to various fields such as automotive parts, seals, medical equipment, transportation and communications. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0037] Figure 1-Figure 2 This is an electron microscope image of the nano-starch prepared in Example 1.
[0038] Figure 3 This is a picture of the hydrophobic angle of the nano-scale hydrophobic starch prepared in Example 1.
[0039] Figure 4 This is a picture of gelatinized starch in the comparative example.
[0040] Figure 5 This is the cross-sectional electron micrograph of sample 1. DETAILED DESCRIPTION
[0041] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. The materials involved in the following examples can be obtained from commercial channels unless otherwise specified. The methods described are conventional methods unless otherwise specified.
[0042] Styrene-butadiene rubber: SBR-1502, Kunlun; hexadecyltrimethoxysilane: 16415-12-6, Aladdin; starch, stearic acid, zinc oxide and other reagents are all commercially available industrial products.
[0043] Example 1
[0044] (1) Nano-size starch: Place a 15% starch water suspension in a 98°C constant temperature water bath and stir for 30 minutes to obtain a translucent starch paste. Lower the temperature of the constant temperature water bath to 58°C, add 10 ASPU / g α-amylase, and continue enzymatic hydrolysis for 6 hours. Then place the system in a 4°C refrigerated condition for 24 hours, and then place it in a 98°C constant temperature water bath for secondary gelatinization for 1 hour to obtain a secondary starch paste. Pour the secondary starch paste into a large amount of ethanol-water solution (ethanol-water volume ratio 4:1) to separate the nano-size starch. The prepared nano-size starch was scanned by electron microscopy, and the results are shown in Figure 1-Figure 2As can be seen from the figure, the nano-scale starch particles prepared by the present invention have uniform particle size distribution and are not easy to agglomerate.
[0045] (2) Hydrophobic modification of nano starch: adjust the pH of ethanol aqueous solution (ethanol-water volume ratio 4:1) to 4 with acid solution, add hexadecyl trimethoxysilane (HDS) at a mass concentration of 2.5‰, stir and hydrolyze for 2 hours to obtain a hydrolyzate; add 5 parts by mass of nano starch to 100 parts by mass of the above hydrolyzate and stir and react for 2 hours, centrifuge, vacuum dry at room temperature to remove water and ethanol, and then heat to 120°C in a nitrogen atmosphere for 2 hours to obtain nano hydrophobic starch. The hydrophobic angle of the prepared nano hydrophobic starch is tested, and the results are shown in Figure 3 As can be seen from the figure, the nano-scale hydrophobic starch prepared by the present invention has good hydrophobic properties.
[0046] Example 2
[0047] (1) Nano-size starch: Place a 10% starch water suspension in a 95°C constant temperature water bath, stir for 40 minutes, and obtain a translucent starch paste. Lower the temperature of the constant temperature water bath to 58°C, add 7 ASPU / g β-amylase, and continue enzymolysis for 6 hours. Then place the system in a 4°C refrigerated condition for 48 hours, and then place it in a 95°C constant temperature water bath for secondary gelatinization for 0.5 hours to obtain a secondary starch paste. Pour the secondary starch paste into a large amount of ethanol solution, and separate the nano-size starch. The prepared nano-size starch was scanned by electron microscope. The results showed that the nano-size starch particles prepared by the present invention had a uniform particle size distribution and were not easy to agglomerate.
[0048] (2) Hydrophobic modification of nano starch: adjust the pH of ethanol aqueous solution (ethanol-water volume ratio 4:1) to 5 with acid solution, add hexadecyltrimethoxysilane (HDS) at a mass concentration of 2.5‰, stir and hydrolyze for 2 hours to obtain a hydrolyzate; add 5 parts by mass of nano starch to 100 parts by mass of the above hydrolyzate and stir and react for 2 hours, centrifuge, vacuum dry at room temperature to remove water and ethanol, and then heat to 120°C in a nitrogen atmosphere for 2 hours to obtain nano hydrophobic starch. The hydrophobic angle of the prepared nano hydrophobic starch was detected, and the results showed that the prepared nano hydrophobic starch had good hydrophobic properties.
[0049] Example 3
[0050] (1) Nano-size starch: Place a 12% starch water suspension in a 92°C constant temperature water bath and stir for 60 minutes to obtain a translucent starch paste. Lower the temperature of the constant temperature water bath to 58°C, add 9 ASPU / g isoamylase, and continue enzymolysis for 6 hours. Then place the system in a 4°C refrigerated condition for 36 hours, and then place it in a 92°C constant temperature water bath for secondary gelatinization for 1 hour to obtain a secondary starch paste. Pour a large amount of ethanol-water solution (ethanol-water volume ratio 3:2) into the secondary starch paste to separate the nano-size starch. The prepared nano-size starch was subjected to electron microscopy scanning. The results showed that the nano-size starch particles prepared by the present invention had a uniform particle size distribution and were not easy to agglomerate.
[0051] (2) Hydrophobic modification of nano starch: adjust the pH of ethanol aqueous solution (ethanol-water volume ratio 4:1) to 6 with acid solution, add hexadecyltrimethoxysilane (HDS) at a mass concentration of 3‰, stir and hydrolyze for 2 hours to obtain a hydrolyzate; add 6 parts by mass of nano starch to 100 parts by mass of the above hydrolyzate and stir and react for 2 hours, centrifuge, vacuum dry at room temperature to remove water and ethanol, and then heat to 120°C in a nitrogen atmosphere for 2 hours to obtain nano hydrophobic starch. The hydrophobic angle of the prepared nano hydrophobic starch was detected. The hydrophobic angle of the nano hydrophobic starch was maintained above 100° within 300 seconds. The results show that the nano hydrophobic starch prepared by the present invention has good hydrophobic properties.
[0052] Comparative Example 1
[0053] The starch water suspension with a mass concentration of 15% was placed in a 98°C constant temperature water bath and stirred for 30 minutes to obtain a translucent starch paste. The temperature of the constant temperature water bath was lowered to 58°C, 10 ASPU / g α-amylase was added, and the enzymolysis was continued for 6 hours. After the enzymolysis, a large amount of ethanol aqueous solution was directly poured. The nano starches would stick to each other and could not be separated due to the high viscosity. Figure 4 .
[0054] Comparative Example 2
[0055] (1) Nano-size starch: Place a 10% starch water suspension in a 95°C constant temperature water bath, stir for 40 minutes, and obtain a translucent starch paste. Lower the temperature of the constant temperature water bath to 58°C, add 7 ASPU / g β-amylase, and continue enzymolysis for 6 hours. Then place the system in a 4°C refrigerated condition for 48 hours, and then place it in a 95°C constant temperature water bath for secondary gelatinization for 0.5 hours to obtain a secondary starch paste. Pour the secondary starch paste into a large amount of ethanol solution, and separate the nano-size starch. The prepared nano-size starch was scanned by electron microscope. The results showed that the nano-size starch particles prepared by the present invention had a uniform particle size distribution and were not easy to agglomerate.
[0056] (2) Hydrophobic modification of nano starch: The ethanol aqueous solution (ethanol-water volume ratio 4:1) was adjusted to pH 5 with acid solution, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide (Si69) was added thereto at a mass concentration of 2.5‰, and stirred for hydrolysis for 2 h to obtain a hydrolyzate; 5 parts by mass of nano starch was added to 100 parts by mass of the above hydrolyzate, and stirred for reaction for 2 h, centrifuged, and vacuum dried at room temperature to remove water and ethanol, and then heated to 120°C in a nitrogen atmosphere for 2 h to obtain Si69 modified starch.
[0057] In order to detect the reinforcing effect of the nano-scale hydrophobic starch of the present invention on styrene-butadiene rubber, the preparation of reinforced styrene-butadiene rubber according to a conventional formula specifically includes the following steps: adjusting the speed of a closed plastic mixing machine to 30 rpm, setting the temperature to 30°C, and adding 100 parts of styrene-butadiene rubber, 5 parts of zinc oxide, 2 parts of stearic acid, and the hydrophobic nano-starch of Example 1 every 0.5 min under this condition, taking out the rubber material and placing it in an open rubber mixing machine, thinning it 3 times, adding 0.5 parts of accelerator DM; thinning it 3 times, adding 1 part of accelerator CZ; thinning it 3 times, adding 1.5 parts of sulfur, taking the sheet off, placing it for 9 hours, and then vulcanizing it for 40 minutes at 150°C in a flat vulcanizer.
[0058] Different amounts of hydrophobic nano starch of Example 1 were added for reinforcement to obtain styrene-butadiene rubber samples 1 to 3, respectively; styrene-butadiene rubber without starch modification was used as a blank control, and unmodified starch or modified starch of Comparative Example 2 was added as a control. Among them, unmodified starch would strongly adhere to the rotor and inner wall of the internal mixer and could not be blended with styrene-butadiene rubber.
[0059] The tensile strength, elongation at break, 100% elongation stress, and 300% elongation stress of the styrene-butadiene rubber material prepared above were tested. The test results are shown in Table 1. The cross section of sample 1 was observed by scanning electron microscope. The results are shown in Table 1. Figure 5 .
[0060] Table 1
[0061] Sample 1 Sample 2 Sample 3 Blank Contrast Comparative Example 2 Starch / mass 10 20 30 / 20 Tensile strength / MPa 3.33±0.32 4.27±0.60 3.54±0.42 2.00±0.13 2.43±0.32 Elongation at break / % 451±82 517±62 451±63 325±8 402±27 100% tensile stress / MPa 1.16±0.3 1.33±0.04 1.50±0.03 0.97±0.04 1.11±0.01 300% constant tensile stress / MPa 2.12±0.02 2.29±0.05 2.38±0.03 1.86±0.07 1.50±0.07
[0062] Note: Unmodified starch has poor compatibility with styrene-butadiene rubber and cannot be mixed to obtain reinforced samples, so there is no performance data.
[0063] Depend on Figure 5It can be seen that the nano-scale modified starch prepared by the present invention is uniformly dispersed in the styrene-butadiene rubber matrix in nanometer size and has excellent compatibility. Combined with the data in the table, it can be seen that after nano-ization and hydrophobic modification, the starch of the present invention can not only be effectively and uniformly dispersed in the matrix of styrene-butadiene rubber, but also can be used as a reinforcing agent to improve the matrix strength of styrene-butadiene rubber; after reinforcement, the mechanical properties of styrene-butadiene rubber are significantly improved, the tensile strength is increased by more than 110%, the elongation at break is increased by 59%, and the 100% tensile stress and 300% tensile stress are also significantly improved.
[0064] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing nano-scale hydrophobic starch, prepared by nano precipitation method, characterized in that The specific steps include: (1) Nano-size starch: The starch suspension is gelatinized once, and then amylase is added to perform enzymatic hydrolysis under heat preservation. After refrigeration, the suspension is heated again for secondary gelatinization. After the treatment, the system is added to an ethanol solution to separate and obtain nano-size starch. (2) Hydrophobic modification: The nano-sized starch is added to the hydrolyzate of hexadecyltrimethoxysilane and stirred for reaction. After separation and drying, the nano-sized starch is heated under an inert atmosphere to obtain the nano-sized hydrophobic starch.
2. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the starch suspension is 10-15 wt %; and the amount of amylase added is 7-10 ASPU / g starch.
3. The preparation method according to claim 1, characterized in that: In step (1), the insulation temperature is 50-60°C; the enzymatic hydrolysis time is 6-10 hours; and the cold storage treatment is carried out at 2-6°C for 12-48 hours.
4. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the nano-starch to the hydrolyzate is 5:100-10:
100.
5. The preparation method according to claim 1, characterized in that: The mass concentration of hexadecyltrimethoxysilane in the hydrolyzate is 2.5-5‰.
6. The preparation method according to claim 1, characterized in that: In step (2), the hydrolyzate is obtained by adding hexadecyltrimethoxysilane to an ethanol aqueous solution and hydrolyzing for 1-4 hours at a pH of 4-6.
7. The preparation method according to claim 1, characterized in that: In step (2), the heating treatment is carried out at 100-120°C and the treatment time is 1-5h.
8. A nano-scale hydrophobic starch, characterized in that Obtained according to the preparation method according to any one of claims 1 to 7.
9. Use of the nano-scale hydrophobic starch according to claim 8 in reinforcing styrene-butadiene rubber.
10. A reinforced styrene-butadiene rubber, characterized in that The components contain the nano-scale hydrophobic starch described in claim 8.
Citation Information
Patent Citations
Process for moderate-temperature self-assembly preparation of nano starch from enzymolysis short amylose
CN104804200A
Composition containing starch nano particles and preparation method thereof
CN105733211A
Preparation of nano-ethylene rubber composite material
CN109608753A
Natural latex ultrathin condom and preparation method thereof
CN113845704A
Preparation method of modified nano starch, modified starch-based biodegradable elastomer and preparation method of modified starch-based biodegradable elastomer
CN118388714A